Pengaruh Model Problem Based Learning Terintegrasi Video Animasi Terhadap kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII - Rama Duwina Harianja; Ani Minarni (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Abstract. This study aims to determine whether there is an influence of the problem based learning model integrated with video animation on the mathematical problem solving abilities of class VIII students. This research was conducted at SMP Negeri 6 Percut Sei Tuan, TA 2022/2023. The research method used is a quasi-experimental design method. The sample in this study consisted of two classes namelyclass VIII-3 as the experimental class and class VIII-4 as the control class. The experimental class uses a problem-based learning model integrated with video animation and a control class with conventional learning. Obtaining the average score of the final test (posttest) of the experimental class students is equal to 89.22, whereas in the control class the average result of the student's final test score was 72.55, in the hypothesis test, the results obtained from the average difference test (t-test) with statistical values t_hitung>t_tabel(10.56 > 1,671 ) which means there is an influence from the usea problem-based learning model integrated with video animation that is applied to the experimental class. This indicates that the mathematical problem solving abilities of the experimental class students are better than the control class.